Subcutaneous ovarian transplantation for short term preservation in cat - aktham, awban; Baqer J. Hasan, Baqer J. Hasan (University of Thi-Qar Journal of agricultural research, 2025)
An ovarian transplantation procedure in cat carried out without angioanastomosis on 10 donors in aimed of 10 recipient’s cats. The ovaries of donors cats had been removed and sliced then placed in buffer saline followed by histopathological evaluation, transplanted into recipient cats subcutaneously.  One month after surgery, the recipient cats treated with PMSG+hCG hormones to activate the transplanted ovaries. The response to hormonal activation were assessed using two methods, the first was ultrasonographic examination to monitoring follicular development and the second done by estimation of blood estrogen hormone after operation in comparison with before operation. The results show there are significant changes in serum estrogen concentration before and during different times (days) after hormonal treatment of recipient cats in comparison with before treatment which may indicate of ovarian activation containing primary and secondary follicles , this result confirmed by ultrasonography for follicular detection. In conclusion subcutaneous allo-ovarian transplantation could be in immunosuppressed cat with no any visible complications. The study also shows that there are remaining levels of estrogen hormone even after ovariectomy in cat. Finally administration of PMSG + hCG hormone could activate the subcutaneous transplanted ovaries by activation of follicular development